(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
Last November 19th, the third edition of the Rovereto’s “Festival of Meteorology” was successfully completed. The theme of the relationship between science and meteorology played a leading role, establishing itself as a precious opportunity for comparison between experts and enthusiasts of the sector. The Rovereto Civic Museum Foundation has always been one of the organizers of the festival alongside the University of Trento, the Municipality of Rovereto and Trentino Sviluppo. In addition to welcoming and coordinating the educational activities linked to the festival, the museum has also contributed to the set–up of some exhibitions located throughout the city. Dedicated to the storm chasing activity of Valentina Abinanti and hosted by the Civic Library of Rovereto, the photo exhibition “A caccia di tornado” has commanded particular interest. At the same time, the Palazzo dell’Istruzione has hosted the exhibition of the graphic works created by two classes of the “Depero” High School of Rovereto, winners of the national contest “Images for the Earth”. Furthermore, the Trentino Sviluppo headquarters was the setting for “Meteoclick”, an exhibition of the most significant photographs of the amateur competition organized on the occasion of the 2017 “Festival of Meteorology”. All the figurative material linked to these exhibitions offers much food for thought and an in–depth analysis, useful for dealing with the relationship between science and image in the context of the activities carried out at the RCM Foundation, where the meteorology and the astronomy staff operates together. The observation of atmospheric phenomena, in fact, is not limited exclusively to our planet, but it can also occur outside the Earth’s atmosphere, from where an enormous quantity of photographic material comes which is equally suggestive and useful to deepen the theme of meteorology by broadening our horizons to arrive at the most remote places in space.